Multi-Color Channel Gamma Correction in Fringe Projection Profilometry - Xiang Sun; Yunpeng Zhang; Lingbao Kong; Xing Peng; Zhenjun Luo; Jie Shi; Liping Tian (Photonics)
Three-dimensional shape measurement plays an important role in various fields. As a way of three-dimensional measurement, fringe projection profilometry (FPP) is widely used because of its non-contact, simple structure, and high stability. One of the key challenges affecting measurement accuracy is the gamma effect. With the development of FPP technology, multi-color channels are gradually applied to the measurement, and the response of different colors in the projector-camera system (pro-cam system) is not exactly the same. Therefore, more accurate gamma correction for different color channels is required. To solve this problem, a model of joint gamma correction for different color channels is proposed. In this model, the light is subdivided into three channels: red; green; and blue (RGB). In the pro-cam system, the different responses of different colors and the influence of background light intensity on gamma correction are comprehensively considered, and some error compensation is made for color crosstalk. Compared with the traditional gamma correction methods, the gamma correction method proposed in this paper is more accurate and has a larger effective working range after correction. This method is particularly beneficial in scenarios where multiple color channels are used for measurement, as it more accurately reflects the true measurement results for each channel. The effectiveness and accuracy of the method are validated through experiments.